MANAGEMENT OF CULTURAL ENVIRONMENT IN MUNICIPALITY: PROBLEMS AND DEVELOPMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper deals with management system of cultural environment in municipality and emphasise the actuality of its interpretation. The author has made research of built heritage in Tukums town and defined changes in its cultural environment using methods of field research and analysis of documents, town plans and historical photographs. The research resulted on history of each of buildings in the historical centre of town. The author did case analysis of three interpretation methods used to increase cultural, social and economic value of cultural heritage in old town: museum exhibitions, live performances in the monument and interpretive heritage walk.